Casearia tomentosa fruit extracts exposed larvicidal activity and morphological alterations in Culex quinquefasciatus and Aedes albopictus under in vitro and semi field conditions - Priyanka Mandal; Goutam Chandra (BMC Research Notes)
Abstract Mosquitoes are notorious insects that transmit a wide range of infectious diseases, including zika, malaria, chikungunya, filariasis, and dengue. The overuse and incorrect application of synthetic pesticides to control mosquitoes has resulted in resistance development and environmental contamination, both of which have had a negative impact on human health. To address this issue, the larvicidal and pupicidal potential of acetone extract from Casearia tomentosa fruits was investigated. The extract was evaluated in a lab setting against all larval instars and pupa of Culex quinquefasciatus and Aedes albopictus, as well as against third instar larvae in a semi-field condition. Purified compounds through TLC were also tested against 3rd instar larvae of both mosquito and non-target organisms. The FT-IR and GC-MS analyses were used to characterise the extract. Morphological aberration caused by the acetone extract was observed using FESEM. The anal gills and respiratory siphon of both mosquitoes showed significant deformation from their normal state. 100 ppm was found to cause 100% larval mortality at 24 h of exposure in case of Cx. quinquefasciatus and at 72 h of exposure in Ae. albopictus larvae. After 72 h of exposure under in vitro conditions, the extract demonstrated considerable larvicidal activity with LC50 values of 38.33 and 47.56 against 3rd instar larvae of Culex quinquefasciatus and Aedes albopictus, respectively. The acetone extract can be considered as a highly effective mosquito larvicidal agent that is safe for the environment. Graphical abstract